The role of hygiene in prevention of major dental diseases among workers of metallurgical production - S. B. Ulitovsky; O. V. Kalinina; I. A. Butyugin; M. B. Kadyrov (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова, 2015)
This review introduces readers to the problems of improving dental care in workers of metallurgical production and the main methods of prevention of dental diseases. The presented data show the features of the dental status of the surveyed population. The article describes the basic ways of prevention of dental diseases and observance of rules of hygiene of the oral cavity in workers of metallurgical production.